1996
DOI: 10.1111/j.1475-682x.1996.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gender of Audience Building: Televised Coverage of Women's and Men's NCAA Basketball*

Abstract: This article, based upon a comparative analysis of televised coverage of the "Final Four" of the women's and men's 1993 NCAA basketball tournaments, sheds light on some of the mechanisms through which an "audience preference" is socially constructed for men's sports over women's sports. First, we examine the temporal framing of the women's and men's tournaments by the sportshedia complex. Next, we present a comparative description of the visual and verbal televised presentation of the women's and men's games. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Because a large number of readers for the magazine are sports minded women, perhaps the editors have recognized this large potential market and plan to offer them a more realistic view of female athletes. As Messner et al (1996) suggested, perhaps capitalistic ventures have "won out" over the maintenance of patriarchy in this situation. That is, due to the proliferation of active females since the passing of Title IX, the media may be arduously constructing audiences for women's sports in order to take full monetary advantage of this societal change.…”
Section: Sports Illustrated For Womenmentioning
confidence: 99%
“…Because a large number of readers for the magazine are sports minded women, perhaps the editors have recognized this large potential market and plan to offer them a more realistic view of female athletes. As Messner et al (1996) suggested, perhaps capitalistic ventures have "won out" over the maintenance of patriarchy in this situation. That is, due to the proliferation of active females since the passing of Title IX, the media may be arduously constructing audiences for women's sports in order to take full monetary advantage of this societal change.…”
Section: Sports Illustrated For Womenmentioning
confidence: 99%
“…This wrestler indicates admiration for the female wrestler's accomplishments, which he assumes would be much more celebrated if the wrestler had been a male. This finding may be explained in terms of the media's attention to audience building and the mechanisms through which an "audience preference" is socially constructed for men's and women's sport (Messner, Duncan, & Wachs, 1996). One typical justification for less media coverage of women's sports relates to "supply and demand" based on the assumption that the sport audience is composed mostly of men who show little interest in women's sports.…”
Section: Local Press Versus National Press and Tv Coverage Of Wrestlingmentioning
confidence: 99%
“…Those who lament the lack of coverage of women's sports often face the argument that disparities between the coverage of men's and women's sporting events exist due to media outlets giving their target market what it wants (Brennen 2005;Kinkhabwala 2007). Messner et al (1996) noted that media producers believe they operate on the principles of supply and demand and therefore the differences in television ratings between men's and women's events simply confirm consumers are not very interested in women's sports.…”
Section: Introductionmentioning
confidence: 95%
“…Much of the research has focused on the quantitative and qualitative disparities between the presentation of men's and women's sporting events (Messner et al 1996(Messner et al , 2003Weiller and Higgs 1999;Elueze and Jones 1998;Higgs et al 2003;Eastman and Billings 1999;Hardin et al 2002) and the marginalization of women's sport through differential framing (Eastman and Billings 2000;Messner et al 1993Messner et al , 2000. Those who lament the lack of coverage of women's sports often face the argument that disparities between the coverage of men's and women's sporting events exist due to media outlets giving their target market what it wants (Brennen 2005;Kinkhabwala 2007).…”
Section: Introductionmentioning
confidence: 99%